Proteome profiling of human lung epithelial cells unveils distinct patterns of protein expression in response to SARS-CoV-2 ORF3a - Apoorva; Astha Shukla; Atul Kumar; Saurabh Singh; Sunit K. Singh (The Microbe)
The COVID-19 pandemic caused by SARS-CoV-2 remains an ongoing global health concern. Understanding the roles of SARS-CoV-2 accessory proteins is essential for developing effective therapeutic strategies. We present a comprehensive proteomic analysis of human lung epithelial cells in response to SARS-CoV-2 ORF3a. Through, the high-resolution mass spectrometry analysis, we observed significant alterations in the cellular proteome of human lung epithelial cells transfected with SARS-CoV-2 ORF3a. We identified a total of 56 proteins with differential expression patterns. Among these, 17 proteins showed upregulation, while 39 proteins exhibited downregulation in response to SARS-CoV-ORF3a. The pathway enrichment analysis led to the identification of proteins like NEU1, CTSH, ABCE1, Nup155, and KLC1, having important roles in innate immunity, adaptive immunity, cytokine signaling, and antiviral mechanisms. Furthermore, the protein-protein interaction (PPI) network analysis revealed USP10, HELZ, and EXOSC4 as hub proteins. These proteins may play a role in modulating the host's cellular immune functions in response to SARS-CoV-2 ORF3a. Taken together, the present study demonstrates key proteins involved in ORF3a-mediated dampened immune response in human lung epithelial cells, which may facilitate viral replication. These findings may pave the way for understanding the molecular pathogenesis of SARS-CoV-2 and developing novel therapeutic interventions targeting viral accessory proteins.